Comparing Otoliths and Scales as Structures Used to Estimate Ages of Largemouth Bass: Consequences of Biased Age Estimates. (25th July 2017) - Tyszko, Stephen M.; Pritt, Jeremy J.
Abstract: Management agencies often estimate the ages of Largemouth Bass Micropterus salmoides based on the examination of scales—a structure that is known to produce biased estimates—without knowing how the associated bias affects management decisions. We sought to understand the effects of this bias by comparing population metrics that were predicted using scale‐derived and otolith‐derived age data. We collected scales and otoliths from Largemouth Bass that were sampled during standard electrofishing surveys. The age of each fish was estimated independently by three separate readers using both scales and otoliths. We assessed the average coefficient of variation for scale‐derived and otolith‐derived age estimates, examined the bias of scale‐derived age estimates, and estimated von Bertalanffy growth model parameters by using ages estimated from scales and otoliths. These parameter estimates were used in yield‐per‐recruit simulations that predicted yield and the percentage of individuals in the cohort surviving to 380 mm (proportional size distribution [PSD] 380) or to 470 mm (PSD 470) at several levels of natural mortality and fishing mortality. Otolith‐derived age estimates were more precise; scale‐derived age estimates showed significant positive bias for fish younger than age 6 and significant negative bias for fish older than age 6. Von Bertalanffy parameter estimates were significantly different when using ages estimated from scales and those estimated from otoliths. Modeling indicated that estimates of yield and PSD 380 resulting from the two structures were similar. However, the use of scale‐derived ages resulted in underestimating the impact of fishing mortality on PSD 470 by as much as five times at low levels of natural mortality and fishing mortality. Our estimates of precision and bias were similar to other comparisons of scales and otoliths, and the results of our yield‐per‐recruit simulations are likely generally applicable for Largemouth Bass management. Trophy fishing is a common management objective, and managers relying on scale‐based age data could be less likely to adopt the restrictive harvest regulations that are critical for producing trophy Largemouth Bass. Received November 17, 2016; accepted June 22, 2017 Published online August 22, 2017